Consultoria colaborativa na escola : contribuições da Psicologia para inclusão escolar do aluno surdo - Pereira, Veronica Aparecida (2009)
This study aimed to investigate the psychological procedures in the school environment which may favor the inclusion with the aid of the collaborative consultation. A total of six teachers from regular classes of the first initial years of the Elementary School, 3 of them were hired from the school and 3 were substituting. The teachers authorized the observation of their classes twice a month and also authorized the consultation procedures every other week. There were deaf students in the three classrooms, a total of six students (G1). The consultant asked the teachers to indicate other six students who presented socially accepted behavior (G2) and other six students who presented some behavioral problems (G3); all of them were identified by the employment of two behavioral scales, answered by the teachers. In order to evaluate the school performance, the hearing students and the deaf ones took part in a school performance test. Both, the behavioral scales and the school performance test were reemployed at the end of the school year. From May to December 2006, the consultant realized every 15 days, systematic observation of the classes, in the three classrooms, making observations on the diary. The registered content was discussed on the following week with each teacher, for evaluation and practices planning. At the end of the process, the consulting activity was evaluated as a possibility of baseline, either for the consultant as for the teachers in charge. The behavioral scales enabled the discrimination of socially accepted behavior and orientation for behavioral procedures which have contributed for the enhancement of opportunities. The evaluation of the scholar performance presented a correlation between behavioral problems and learning difficulties, besides indicating that actual procedures have contributed for teaching math to deaf students, but it was not assured yet, at least in that school, the alphabetization, which is an essential requirement for accessibility to the academic knowledge.